2005
DOI: 10.1093/nar/gki706
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of the mouse nuclear export factor (Nxf) family members

Abstract: TAP/hNXF1 is a key factor that mediates general cellular mRNA export from the nucleus, and its orthologs are structurally and functionally conserved from yeast to humans. Metazoans encode additional proteins that share homology and domain organization with TAP/hNXF1, suggesting their participation in mRNA metabolism; however, the precise role(s) of these proteins is not well understood. Here, we found that the human mRNA export factor hNXF2 is specifically expressed in the brain, suggesting a brain-specific ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
47
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(54 citation statements)
references
References 29 publications
7
47
0
Order By: Relevance
“…2, panel d). This pattern resembles that seen in transient transfection experiments using epitope-tagged NXF2 fusion proteins (Herold et al 2000;Tan et al 2005). Further, FMRP and NXF2 colocalize at the perinuclear region in spermatogonia in our double staining immunofluorescence experiments (Fig.…”
supporting
confidence: 84%
See 2 more Smart Citations
“…2, panel d). This pattern resembles that seen in transient transfection experiments using epitope-tagged NXF2 fusion proteins (Herold et al 2000;Tan et al 2005). Further, FMRP and NXF2 colocalize at the perinuclear region in spermatogonia in our double staining immunofluorescence experiments (Fig.…”
supporting
confidence: 84%
“…1A). Metazoans encode additional NXF1 orthologs, including NXF2 (Herold et al 2000;Sasaki et al 2005;Tan et al 2005). The overall domain organization of NXF2 follows a highly conserved modular architecture (Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We found that the human NXF1 bound to RBM15 in vitro, whereas no interactions with luciferase, UAP56 or "empty" GST beads were observed. Similarly, we found that the mouse NXF2, a highly related mRNA export factor (27), interacted with RBM15 (data not shown). The binding assays were performed in the presence of RNase A, demonstrating that the identified interactions of RBM15 with the NXF proteins are RNA-independent.…”
Section: Rbm15 and Nxf1 Bind To Each Other And Actmentioning
confidence: 56%
“…In Vitro Protein Binding Assays-Metabolically labeled reticulocyte-produced proteins were synthesized in a coupled transcription/translation system (TNT T7 Coupled Reticulocyte Lysate System, Promega) and used in binding reactions con- taining ϳ0.5 g of E. coli-produced GST-tagged proteins (27). The binding was performed in 200 l of RBB-400 buffer in the presence of 100 g of RNase A.…”
Section: Methodsmentioning
confidence: 99%